2002
DOI: 10.1002/humu.9062
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of small rearrangements in the factor VIII gene F8C among patients with severe hemophilia A

Abstract: Hemophilia A is a common X-linked bleeding disorder caused by various types of mutations in the factor VIII gene F8C. The most common intron 22-inversion is responsible for about 40% of the severe hemophilia A cases while large deletions, point mutations and small (less than 100 bp) deletions or insertions are responsible for the disease in the rest of patients. We report on nine novel (6 deletions, two indels and one partial duplication) and five recurrent small rearrangements identified in 15 German patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2005
2005
2010
2010

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 42 publications
1
14
0
Order By: Relevance
“…The previously reported recurrent mutation c.3637del A [29], a single nucleotide deletion in a 9 poly-A section of exon 14, was identified in two unrelated patients. The poly-A segment of exon 14 is considered a hotspot for mutations in hemophilia A patients [6,30].…”
Section: Discussionmentioning
confidence: 93%
“…The previously reported recurrent mutation c.3637del A [29], a single nucleotide deletion in a 9 poly-A section of exon 14, was identified in two unrelated patients. The poly-A segment of exon 14 is considered a hotspot for mutations in hemophilia A patients [6,30].…”
Section: Discussionmentioning
confidence: 93%
“…The molecular analyses of 21 of these cases were previously published [Bogdanova et al, 2001[Bogdanova et al, , 2002Leuer et al, 2001] and the remaining 65 patients were analyzed in the present work. All of the individuals were affected by severe hemophilia A according to the standard criteria [Antonarakis et al, 1995], including one person (PL) [Bogdanova et al, 2001] who had severe hemophilia A and was initially incorrectly reported to us as being moderately affected.…”
Section: Methodsmentioning
confidence: 99%
“…All four inhibitor-positive patients (the previously published individuals NB2, NB56, and NB58 [Bogdanova et al, 2002], and NB253 (c.3385delC, exon 14)) carried small deletions in exon 14 of the F8 gene. Thus the inhibitorpositive cases represented 4.6% of our patient cohort.…”
Section: Development Of F8 Inhibitorsmentioning
confidence: 98%
See 2 more Smart Citations